Photovoltaic properties of Au/?-carotene/n-Si organic solar cells - Yakuphanoğlu, Fahrettin; Aydin, M. E.; Kilicoglu, T. (Amer Chemical Soc, 2006)
Photovoltaic properties of Au/beta-carotene/n-Si organic solar cells characterized by current-voltage and capacitance-voltage measurements have been investigated. The photocurrent in the reverse direction increases with increasing illumination intensity. The I-sc increases linearly with light intensity. The I-sc dependence of light intensity follows a power law I-sc similar to F-alpha. The exponent alpha was found to be 1.38. This indicates a monomolecular recombination in this device. Au/beta-carotene/n-Si organic solar cells give an open-circuit voltage of 0.316 V and a short-circuit current of 2.33 x 10(-4) A at light intensity of 6 W/m(2). The best conversion efficiency for Au/beta-carotene/ n-Si solar cells was found to be 23.3% at a light intensity of 6 W/m(2).